Impact of subclinical and clinical mastitis on sensitivity to pain of dairy cows. (29th July 2015) - Peters, M. D. P.; Silveira, I. D. B.; Fischer, V.
Abstract : A total of 90 cows from three commercial farms were used to evaluate the relationship between subclinical mastitis and clinical mastitis and thermal nociceptive threshold. Milk strips from all udder quarters were tested for clinical mastitis with visual inspection of milk and udder alterations and for subclinical mastitis using California Mastitis Test. Milk yield was recorded, milk was sampled and further analyzed for somatic cells count (SCC). Cows were considered healthy when SCC<200 000 cells/ml and no visual alterations in milk and/or udder, with mild subclinical mastitis when SCC>200 000 cells/ml and no visual alterations in milk and/or udder, with moderate subclinical mastitis when SCC>500 000 cells/ml and no visual alterations in milk and/or udder and with clinical mastitis when visual alterations in milk and/or udder were detected. Nociceptive threshold was evaluated with the thermal threshold meter apparatus applied to the rear legs. Thermal threshold (TT) decreased when we compared healthy cows with cows presenting clinical mastitis and tended to decrease when we compare healthy cows with those with moderate subclinical mastitis. TT was lower at the ipsilateral rear leg compared with the contralateral leg to the infected mammary gland. TT linearly decreases aslog10 SCC increased and it showed sharp decrease aslog10 SCC exceed the value of 6.4. Increase in one unit oflog10 SCC increased the odds of low thermal threshold (lower than 55.8°C). Subclinical mastitis might be a welfare issue as it tended to decrease nociceptive thermal threshold.